THIRD-ORDER NONLINEAR OPTICAL RESPONSE AND OPTICAL LIMITING BEHAVIOR OF 3,4-DIAMINOPYRIDINE - Abdulameer Imran; Qusay M. Ali Hassan; Hussain A. Badran (European Scientific Journal, ESJ, 2014)
In This paper is reported the experimental investigation on thirdorder nonlinear optical parameters of a 3,4-Diaminopyridine in solvent DMSO by using Z-scan technique. The measurements were performed using cw from a solid state laser at 473 and 532 nm wavelengths. The results reveal that 3,4-Diaminopyridine exhibits large negative nonlinear refractive index,n2,of the order of 10-7 cm2/W. The nonlinear optical properties were found to vary with concentration and wavelength. Also it was found that the 3,4-Diaminopyridine in solvent DMSO exhibits good optical power limiting. This 3,4-Diaminopyridine has potential application as photonic and optoelectronic devices.